Characterization of trazodone metabolic pathways and species-specific profiles - Petrucci, Vanessa; Dragone, Patrizia; Laurenti, Marcello C.; Oggianu, Laura; Zabela, Volha; Cattaneo, Agnese (Frontiers in Pharmacology, 2025)
BackgroundTrazodone, an antidepressant indicated for the treatment of major depressive disorder (MDD), undergoes complex metabolism involving multiple cytochrome P450 (CYP) isoforms. Despite its widespread clinical use, there is limited contemporary research on trazodone biotransformation, particularly regarding interspecies differences mediated by CYP enzymes. This study investigates the hepatic metabolic stability, pathways, and inhibitory effects of trazodone and its metabolites.MethodsThe hepatic metabolic stability of trazodone was evaluated in cryopreserved hepatocytes from human, mouse, and rat sources. Metabolic profiling was conducted using human and rat liver microsomes, hepatocytes, and rat plasma to identify primary and secondary metabolites. CYP isoforms involved in trazodone metabolism were identified through selective CYP inhibitors and recombinant enzymes. Additionally, the inhibitory potential of trazodone and m-chlorophenylpiperazine (mCPP) —the only pharmacologically active metabolite—on CYP enzymes was assessed in both human and mouse hepatocytes.ResultsTrazodone demonstrated significant interspecies differences in intrinsic clearance rates, with human hepatocytes exhibiting the slowest conversion, suggesting prolonged exposure and potential for stable plasma levels. CYP3A4 was identified as the primary enzyme mediating trazodone metabolism, particularly in the formation of mCPP while CYP2D6, CYP2C19, and FMOs contributed to the formation of other major, inactive metabolites such as M9 and M2.ConclusionCYP3A enzymes were identified as the primary mediators of trazodone metabolism, particularly for the formation of its only active metabolite, mCPP, with additional contributions from CYP2D6, CYP2C19, and FMOs to other pathways. Interspecies differences were most pronounced for CYP3A-mediated metabolism and hepatic clearance, reinforcing the importance of human-specific models to characterize trazodone’s pharmacokinetics. These findings advance the understanding of its biotransformation and support its optimized clinical use in major depressive disorder—particularly in complex therapeutic regimens and genetically diverse populations.